Poly(2,5-Benzimidazole)-based flat sheet membranes: investigating effects of dope solvent and membrane heat treatment on forward osmosis and acid enrichment performances - Somkuwar, Nitin C.; Thorat, Nitin M.; Ambade, Ashootosh; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2026)
The present work investigates two methods for preparing defect-free, symmetric membranes of the thermochemically robust polymer, poly(2,5-benzimidazole) (commonly known as ABPBI) for forward osmosis (FO), a growing technology for niche separations. The obtained polymer and membranes were analyzed for physical properties of significance. The FO analysis was performed using three salt solutions, viz., sodium chloride (NaCl), magnesium chloride (MgCl2), and sodium sulfate (Na2SO4). The effects of casting methodology (solvents present in the dope), membrane heat treatment, draw solution concentration, long-duration analysis, and FO-assisted enrichment of organic acids were evaluated. Some of the membranes exhibited extremely low reverse salt flux (RSF), which conveys the novelty of these membranes. Some of these membranes were analyzed using a high draw solution (DS) concentration (4 mol L-1) to enhance water flux and further employed to enrich organic acids. The aqueous acetic and methacrylic acid concentrations were enriched from 4.89 and 2.93 mol L-1 to 11.88 and 10.01 mol L-1, respectively. These results demonstrate an unmet need of concentrating methacrylic acid (a temperature-sensitive compound possessing a double bond). The present work demonstrates the potentials of ABPBI-based symmetric, thin membranes for FO and their industrial applicability for the first time.
Keywords: Applications; membranes; separation techniques